2018
DOI: 10.1186/s12937-018-0424-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between eating behaviour and diet quality: eating alone vs. eating with others

Abstract: BackgroundTo discover the association between eating alone and diet quality among Korean adults who eat alone measured by the mean adequacy ratio (MAR),MethodsThe cross-sectional study in diet quality which was measured by nutrient intakes, indicated as MAR and nutrient adequacy ratio (NAR) with the Korean National Health and Nutrition Examination Survey (KNHANES) VI 2013–2015 data. Study population was 8523 Korean adults. Multiple linear regression was performed to identify the association between eating beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 44 publications
2
35
2
5
Order By: Relevance
“…Today, followed by the breakdown of the traditional family culture, single person households increased significantly in Korea [7,8]. As a result, eating alone has become a popular new trend that myriad restaurants even provide special seats and menus for single customers [9,10]. When having family dinner, people tend to focus more on the food that they usually consume and subsequently keep their proper amount [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, followed by the breakdown of the traditional family culture, single person households increased significantly in Korea [7,8]. As a result, eating alone has become a popular new trend that myriad restaurants even provide special seats and menus for single customers [9,10]. When having family dinner, people tend to focus more on the food that they usually consume and subsequently keep their proper amount [19].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, single person households in Korea are expected to further increase, reaching 37.3% of total households in 2047 [8]. In conjunction with these statistics, eating alone is becoming a popular new trend in Korea [9]. An increased amount of restaurants are encouraging these emerging dietary patterns by providing special seats for single customers, reflecting the fact that, no matter a person's sex, age, or occupation, eating alone has become increasingly popularized [10].…”
Section: Introductionmentioning
confidence: 99%
“…Selain penggunaan aplikasi pesan antar makanan online, perilaku makan dapat dipengaruhi oleh beberapa faktor yang selanjutnya berdampak pada kualitas diet. 29 Menurut teori Lawrence Green, ada 3 faktor utama penentu perilaku yaitu faktor predisposisi, pemungkin dan penguat. Faktor predisposisi yang telah dianalisis dalam penelitian ini meliputi agama, jenis kelamin, daerah asal dan pengetahuan gizi namun hasilnya tidak memiliki hubungan terhadap frekuensi makan dan kualitas diet.…”
Section: Hubungan Penggunaan Aplikasi Pesan Antar Makanan Online Dengunclassified
“…It has been demonstrated that older adults who eat meals in the company of others have better dietary quality [17,18]. Hence, the family and caregivers of these older adults should organize a schedule to be present during mealtimes using social media.…”
Section: Palavras-chave: Idosos Infecções Por Coronavirus Nutriçãomentioning
confidence: 99%